Sebuah Analisis Kritis terhadap Peran Organisasi Muhammadiyah dalam Transformasi Sosial Indonesia - Misbahul Munir; Zainal Arifin (PT. Kreasi Karya Majakata, 2026)
Since its establishment in 1912, the Muhammadiyah organization has positioned education as the primary vehicle for religious outreach and social mobilization. This article critically analyzes how Muhammadiyah educational institutions function not merely as formal learning institutions but also as instruments of social change that provide access to social mobility for society. Managing over 17,000 educational institutions at various levels, Muhammadiyah has created a learning ecosystem that integrates Islamic values with community empowerment. Using a critical analytical approach, this research identifies mechanisms of social transformation through education, including the roles of curriculum, extracurricular activities, and social programs in mobilizing community resources. Findings reveal that while Muhammadiyah has made significant contributions to social mobility and national human resource provision, there are critical challenges to be addressed: the gap between dakwah idealism and institutional practice, dependence on religious orientation that may limit inclusivity, and the need for deeper evaluation of long-term qualitative impact. This article concludes that Muhammadiyah must continue critical reflection on its model to remain relevant within the changing national educational context.